VIETNAMESE - K’HO MACHINE TRANSLATION USING EBMT APPROACH - Nguyễn Minh Tuấn; Đinh Viết Tuấn (Tạp chí Khoa học Đại học Đà Lạt)
This paper proposes the Example Based Machine Translation (EBMT) method for Vietnamese-K’Ho machine translation. Both Vietnamese and K’Ho are linguistically rooted in the South Asia but they belong to different language groups; therefore, Vietnamese-K’Ho or vice versa translation are widely conducted by exploiting vocabulary, phrases and sentences instead of the general syntax rules. The design principles of the application are described in details, along with the system interface. The machine translation results are also presented to illustrate the applicability of the EBMT method.